A bacterial effector manipulates host lysosomal protease activity–dependent plasticity in cell death modalities to facilitate infection - Zhe Lu; Yong Zhang; Yanzhao Zhong; Lihua Qiang; Pupu Ge; Zehui Lei; Mengyuan Zhao; Yingxu Fang; Bingxi Li; Jing Wang; Qiyao Chai; Cui Hua Liu (Proceedings of the National Academy of Sciences, 2025)
Crosstalk between cell death programs confers appropriate host anti-infection immune responses, but how pathogens co-opt host molecular switches of cell death pathways to reprogram cell death modalities for facilitating infection remains largely unexplored. Here, we identify mammalian cell entry 3C (Mce3C) as a pathogenic cell death regulator secreted by Mycobacterium tuberculosis (Mtb), which causes tuberculosis featured with lung inflammation and necrosis. Mce3C binds host cathepsin B (CTSB), a noncaspase protease acting as a lysosome-derived molecular determinant of cell death modalities, to inhibit its protease activity toward BH3-interacting domain death agonist (BID) and receptor-interacting protein kinase 1 (RIPK1), thereby preventing the production of proapoptotic truncated BID (tBID) while maintaining the abundance of pronecroptotic RIPK1. Disrupting the Mce3C–CTSB interaction promotes host apoptosis while suppressing necroptosis with attenuated Mtb survival and mitigated lung immunopathology in mice. Thus, pathogens manipulate host lysosomal protease activity–dependent plasticity in cell death modalities to promote infection and pathogenicity.